Dosimetry Characterization of Unknown Dye Polyvinyl Alcohol Films - Muhammad Attique Khan Shahid,; Noureen Kousar,; Naseem Akhtar,; Taqmeem Hussain,; Mariam Saeed Awan,; Arfa Mubashir,; Bushra Bashir ,; Asif Javed, (Journal of Basic & Applied Sciences, 2021)
In the present study chemical dosimeters having aqueous solutions of crystal violet commercial dye were irradiated by Co60 γ source in the range (0-120)KGy. The standard aqueous solutions were scanned by UV/VIS spectrophotometer for the determination of maximum wave length (λmax) which was found to be 591nm at this value maximum absorbance was found to be 3.5; it was also observed that with increase in dose, absorbance decreases correspondingly. At this value, the absorbance (A) of irradiated samples was measured in UV region. The plot between concentration C and A gave approximate linear relationship and hence verified Beer’s Law which proved that these dye solutions can satisfactorily be used as the dye dosimeters in 0-120kGy gamma dose range.